2008
DOI: 10.1111/j.1600-051x.2008.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐11, interleukin‐1β, interleukin‐12 and the pathogenesis of inflammatory periodontal diseases

Abstract: Our data showed that IL-11 levels are significantly decreased in GCF from sites with periodontitis compared with G and healthy sites. Because of the possible preventive effect of IL-11 on inflammation, IL-11 may be an important factor in the therapeutic modulation of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 45 publications
4
65
1
5
Order By: Relevance
“…It has been proposed that an 9 increase in IL-12 production could be an event associated with the inhibition of pro inflammatory cytokines, such as TNF-α (47). IL-12 is considered a link between innate and adaptive immunity (48,49), and may be related to the pathogenesis of periodontal disease (50)(51)(52). Another interesting observation in the present study is that the production of the anti-inflammatory cytokine IL-10 was increased in response to LDD, possibly potentiating its beneficial effects to the host (53).…”
Section: Actinomycetemcomitans Lps (42) In Other Experimental Systemsupporting
confidence: 52%
“…It has been proposed that an 9 increase in IL-12 production could be an event associated with the inhibition of pro inflammatory cytokines, such as TNF-α (47). IL-12 is considered a link between innate and adaptive immunity (48,49), and may be related to the pathogenesis of periodontal disease (50)(51)(52). Another interesting observation in the present study is that the production of the anti-inflammatory cytokine IL-10 was increased in response to LDD, possibly potentiating its beneficial effects to the host (53).…”
Section: Actinomycetemcomitans Lps (42) In Other Experimental Systemsupporting
confidence: 52%
“…Immune response of the periodontal tissues to infection is influenced by environmental factors as well as genetic factors (1). The complex cytokine network that mediates the immune response includes pro-inflammatory cytokines, antiinflammatory cytokines and specific cytokine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have attempted to determine the IL-12 profile in periodontal disease [24][25][26]. Although the results are contradictory, there is evidence that IL-12 plays a potential role in the progression of periodontal inflammation by inducing a Th1 response [26,27].…”
Section: The Role Of Th1/th2/th17 Cytokines In Periodontal Diseasementioning
confidence: 99%
“…It was reported that the twice-weekly administration of recombinant human IL-11 in the developing periodontal disease model acted by blocking the cytokines most associated with inflammation, leaded to a reduction in both attachment loss and bone resorption [50]. In a study which we aimed to determine the possible role of IL-11 in periodontal pathogenesis, together with the proinflammatory cytokines IL-1β and IL-12, lower levels of IL-11 were detected in GCF of chronic periodontitis patients in comparison with gingivitis and healthy subjects [26]. Moreover, IL-11: IL-1β ratio became progressively lower with increasing probing depth.…”
Section: Th2 Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation